Corruption, Corruptors, Indonesia, and Pancasila: Various Current Views - Hilsania, Safa Agrita (Jurnal Scientia Indonesia, 2018)
Corruption is one of the problems that is very difficult to overcome in Indonesia. Since the reign of President Sukarno, who was the first president of Indonesia, corruption has been happening so much that corruption in Indonesia is no longer a secret. When there is someone who is found to do corruption, many television stations and news preach everything about corruption that is happening. Because corruption in Indonesia is very common, this results in most people assuming that corruption is no longer a violation of the law, but as a habit. In addition, it also causes the corruptors, or someone who commits corruption, is not ashamed to commit a corruption act. In fact, they know that corruption is a criminal offence that violates the law and has the values of Pancasila. Because the law has not been able to prevent the corruptors not to commit acts of corruption, the enforcement of the values of Pancasila that has been ruled out needs to be reestablished, because besides being the basis of the country, Pancasila is also a state of ideology that has a source of anti-corruption values that will make people shy to commit corruption.